Physical Education And Sports Activity And Skills In School Pupils - M.A.Ruzimbaev; Mansurov Sh.Sh (International Journal on Economics, Finance and Sustainable Development (IJEFSD), 2021)
The article focuses on the organization of classes with school-age students, the development of interest and skills in physical education and sports in school students, research on the topic